2019
DOI: 10.3389/fimmu.2019.01321
|View full text |Cite
|
Sign up to set email alerts
|

L-Selectin Enhanced T Cells Improve the Efficacy of Cancer Immunotherapy

Abstract: The homing molecule, L-selectin (CD62L), is commonly used as a T cell activation marker, since expression is downregulated following engagement of the T cell receptor. Studies in mice have shown that CD62L + central memory T cells are better at controlling tumor growth than CD62L − effector memory T cells, while L-selectin knockout T cells are poor at controlling tumor growth. Here, we test the hypothesis that T cells expressing genetically modified forms of L-sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 54 publications
1
43
0
Order By: Relevance
“…Vlad et al revealed that CD62L is downregulated in chronic lymphocytic leukemia and associated with disease progression [ 34 ]. Additionally, CD62L can enhance the efficacy of tumor immunotherapy for cancer treatment [ 35 ]. In bladder cancer, the serum level of SELL has been found to be useful as a tool for diagnostic staging and grading [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vlad et al revealed that CD62L is downregulated in chronic lymphocytic leukemia and associated with disease progression [ 34 ]. Additionally, CD62L can enhance the efficacy of tumor immunotherapy for cancer treatment [ 35 ]. In bladder cancer, the serum level of SELL has been found to be useful as a tool for diagnostic staging and grading [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sustained L-selectin expression on NK cells was shown to control tumor progression (39). Recently, the role of L-selectin on T cells was investigated in a transgenic mouse model that expressed non-cleavable L-selectin (40). T cells with constitutive expression of L-selectin suppressed lung metastasis.…”
Section: Selectins Contribute To Cancer Progressionmentioning
confidence: 99%
“…The existence of PD-1+ TIL cells may indicate potential sensitivity to ICI. Preclinical data suggest that the combination of ICI with TIL-ACT can synergistically increase T cell cytolytic ability, effector molecule synthesis, and tumor infiltration, leading to greater tumor control and improved survival [ 95 , 96 , 97 , 98 ]. In one case study, combinatory treatment of TIL and a PD-1 inhibitor led to complete regression of all six metastases in a patient with metastatic breast cancer [ 99 ].…”
Section: Combination Treatmentsmentioning
confidence: 99%